Age-related variations in physical activity, happiness, and psychological well-being: Evidence from Iran - Mohammad VaezMousavi; Lara Carneiro; Amir Shams; Hamed Abbasi; Parvaneh Shamsipour Dehkordi; Mahdi Bayati; Hadi Nobari (PLoS ONE, 2025)
Background Physical activity (PA) is associated with higher levels of PWB and happiness. The high prevalence of physical inactivity among the Iranian population is concerning. Moreover, according to the Happiness Report 2024, Iran is ranked 100th out of 143 countries. Thus, this research aimed to study the PWB, happiness, and PA in Iranian age groups. Methods The study sampled 1,050 participants, equally divided into young, middle-aged, and elderly groups, using randomized cluster sampling from urban areas across five geographic regions in Iran. The study utilized four questionnaires: a Demographic Information Questionnaire, the International Physical Activity Questionnaire (IPAQ), Ryff’s Scales of PWB (18-item form), and the Oxford Happiness Questionnaire (OHQ). Descriptive statistics were used for summarizing data, and inferential analyses included Pearson’s correlation coefficient, one-way ANOVA, the Bonferroni test, and multivariate regression, all with a significance level set at P<0.05. Results Middle-aged individuals had the highest PA (1015.69±730.63 MET-minutes per week) and reported the highest happiness (111.97±24.08) and PWB (63.75±11.17) levels. The elderly had the lowest levels of PA (677.78±592.50 MET-minutes per week), happiness (107.63±24.01), and PWB (60.05±10.02). Statistical tests showed significant differences in PA, happiness, and PWB between the age groups (P<0.05), with no significant difference between young and elderly in PA (P>0.05). Physical activity positively correlated with happiness and PWB, especially in the elderly. Multivariate regression revealed that PA significantly predicts happiness (F = 30.993, t = 6.96, B = 0.211) and PWB (F = 86.85, t = 9.32, B = 0.004), explaining 4.4% and 8.0% of their variances, respectively. Conclusions The study concludes that increasing PA enhances happiness and PWB. Practical applications include promoting PA to improve mental health and PWB. Future research should investigate the effects of specific types of PA and explore longitudinal impacts on PWB to provide a deeper understanding of these relationships.